PELATIHAN MANAJEMEN KEHUMASAN SEKOLAH BAGI SEKOLAH MENENGAH KEJURUAN (SMK) NEGERI 4 PEKANBARU - Ulmi Marsya; Johan Faladhin; Dewi Martina (LPPM UMRI, 2018)
Vocational High School (SMK) is held as a secondary school from SMP / MTs in accordance with their talents, interests and abilities in order to meet the needs / job opportunities that are and will develop in the area. Maximizing the potential of vocational schools can be done by carrying out the public relations function to shape the image and reputation of the school so that it is able to compete with high schools (SMA). Especially in SMK N 4 Pekanbaru which has great potential to be socialized to the public. In connection with the Public Relations Study Program is committed to contributing with institutions including schools to be able to carry out their public relations functions properly.